Analysis of Financial Risks on Indonesian Commercial Banks Return on Asset in 2012 – 2021 - Edwin Setiawan Nugraha; Rosyid Nur Salam (FIRM Journal of Management Studies, 2023)
Financial risks analysis is immensely important for financial institutions since obtaining desirable return at acceptable level of risks is their main objective. Based on Indonesian Banking Statistics, non-performing loans and risk weighted assets have increased annually in Indonesian commercial banks from 2012 to 2021. Additionally, fluctuations in external variables can result in uncertainties which cannot be controlled internally. This work presented analyze the relationship between financial risks such as credit, liquidity, interest rate, inflation, and foreign exchange toward commercial banks return on asset by using multiple linear regression.  The results that independent variables simultaneously have a significant relationship towards return on asset. In addition, some independent variables such inflation rate and liquidity risks have partially positive significant relationship to return on asset while operational risk has negative relationship.  The result of this research will be insight for practitioner in banking as consideration when they are designing the strategy for enhancing their return on asset